Lorenzo Valla's Critique of Jurisprudence, the Discovery of Heraldry, and the Philology of Images. (2019) - Mackenzie, Jennifer Kathleen
Abstract : In 1433, Lorenzo Valla attacked contemporary jurisprudence with a treatise attributed to the civilian lawyer Bartolus of Saxoferrato, the "De insigniis et armis." This was considered Europe's first treatise on heraldry until a team of legal historians questioned its subject matter and authenticity. Meanwhile, visual culture continues to be seen as peripheral to Valla's critical agenda. This article proposes that Valla engaged images as manifestations of social authority and historical change. His epistle against Bartolus participates in an intellectual history of intersections between philology, antiquarianism, and the anthropology of images in which heraldry has been defined.